To Evaluate the Efficacy of Sonic, Ultrasonic, and Manual Irrigation Using Side-Vented Needles for Removal of Metapex Using Different Irrigating Solutions - Trina Mukherjee; Deepak Kurup; Shazia Mahreen; Hetal Khuva; Sourav Tikadar; Hrishita Majumder (Journal of Pharmacy and Bioallied Sciences)
Objective: To evaluate the efficacy of sonic, ultrasonic, and manual irrigation using a side-vented needle for the removal of Metapex with different irrigating solutions. Materials and Methods: Forty-five extracted mandibular premolars were decoronated at 12 mm, and biomechanical preparation was performed up to F2 with thorough irrigation using 5.25% NaOCl between files. Metapex was introduced into the canals, and a precleaning cone beam computed tomography (CBCT) scan was conducted for volumetric analysis of Metapex in the coronal, middle, and apical thirds. Samples were thermocycled for 14 days and then divided into three groups: manual dynamic activation, ultrasonic activation, and sonic activation. After Metapex removal, postcleaning CBCT scans were taken for volumetric analysis. The mean pre- and postcleaning Metapex volumes were calculated for each group and canal third. Statistical analysis was conducted using analysis of variance, with significant results further analyzed by Tukey’s post hoc test (P < 0.05). Results: The mean residual volumes were 79.85, 97.70, and 96.96 in the manual, ultrasonic, and sonic groups, respectively. Post hoc analysis revealed significant differences between the manual and both ultrasonic and sonic groups, with no significant difference between the ultrasonic and sonic groups. Conclusion: Ultrasonic activation is the most efficient method for Metapex removal from root canals.